New developments in early detection of young people at risk of schizophrenia spectrum disorders - Fonseca Pedrero, Eduardo; Paino, Mercedes; Lemos Giráldez, Serafín; Muñiz, José (Anales de Psicología / Annals of Psychology, 2011)
The variety of psychological disorders beginning in early devel-opmental stages have exponentially increased in the last decades, and early detection of these cases is extremely relevant. The aim of this work was to introduce a new self-report for the identification of adolescents at risk of schizophrenia spectrum disorders. For this purpose, an empirical study with 306 adolescents is presented, who were assessed with the preliminary version of the Cuestionario Oviedo para la Evaluación de la Esquizotipia (ES-QUIZO-Q), where it’s psychometric properties are examined. The results indicate that the questionnaire, in this version, shows adequate psycho-metric properties, being a useful instrument for the detection of psychosis proneness. Finally, its applicability in academic settings is suggested, for a quick detection of these risky students and their subsequent derivation to proper services. Future research should continue exploring the role of these instruments for the early identification of students at high risk of different serious psychological diseases.